VD_FINDINFO AM 37/15 - 19/2016 vom 26. April 2016 - VD Tribunal cantonal (2016)
RADIATION DU RÔLE, PROCÈS DEVENU SANS OBJET, RECTIFICATION DE LA DÉCISION | 53 al. 2 LPGA, 53 al. 3 LPGA, 94 al. 1 let. c LPA-VD